The Entrepreneurial Social Cognitive Career Model (ESCCM) Framework in Action: Unpacking Sequential Mediation and Cultural Moderation in Entrepreneurship Education's Impact on Career Choices - Prasetya, Eka Rima; Abdullah, Ade Gafar; Widiaty, Isma (LPPM Universitas Pendidikan Mandalika, 2025)
This study examines how entrepreneurial learning experiences influence students’ career intentions and entrepreneurial actions through psychosocial mediators—self-efficacy, outcome expectations, and interest—and tests whether background contextual support moderates these relationships within the framework of the Entrepreneurial Social Cognitive Career Model (ESCCM). The study employed a quantitative approach with random sampling, involving 1,249 students from 16 universities in Indonesia. Data were collected online over a 10-week period using a structured questionnaire developed based on ESCCM indicators. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate a significant serial mediation effect explaining how Entrepreneurial Learning Experiences (ELE) influence Entrepreneurial Choice Action (ECA), with a cumulative indirect effect of 0.166 across two major mediation pathways. Entrepreneurial Self-Efficacy (ESE) emerged as the strongest mediator, jointly accounting for 65.2% of the variance in ECA. These results emphasize the importance of systematically supporting the development of self-efficacy, outcome expectations, intentions, and goal orientation in entrepreneurship education. The study offers practical implications for designing adaptive entrepreneurship education programs and provides empirical support for the ESCCM framework, which posits that entrepreneurship education shapes career choices through a complex sequence of psychosocial mediators.